Perancangan Website Sebagai Media Informasi Pada Yayasan Pendidikan Darul Ilmi Banyuwangi - Hartono, Rudi; Yulian RL, Dwi; Azzahra, Yasmin; -, Djuniharto (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
The Darul Ilmi Foundation is an institution that organizes educational activities from kindergarten to junior high school. The Darul Ilmi Foundation still uses social media such as Whatsapp, Instagram and Facebook to convey institutional information, which is still not optimal for conveying information on a large scale. There needs to be a website that is able to solve these problems. With a website, information delivery can be done on a large scale and integration between information is easy. The website was built using the PHP and Javascript programming languages and the MySQL database, while the system development method uses the Rapid Application Development (RAD) method which has 3 stages, including system requirements planning, system design process and system implementation. The result of this research is the creation of a website that can accommodate the 5 functional needs of the foundation and can be accessed by the wider community, especially parents of students from the Darul Ilmi Banyuwangi Education Foundation.